Local Wisdom-Based Service Quality Management Strategy to Improve School Image and Teachers' Adversity Quotient: Manajemen Pendidikan - Ahmad Arif Fadilah; Achmad Fauzi; Suhendra; Sholihin (Journal of Pedagogy and Education Science, 2026)
This study investigates the role of local wisdom–based service quality management in enhancing sustainable educational quality through school image and teachers’ adversity quotient (AQ). The study addresses the limited empirical evidence integrating local wisdom into educational service quality management to support sustainable school development. The objective was to examine the influence of local wisdom on service quality management, school image, teachers’ adversity quotient, and sustainable educational quality. A quantitative explanatory survey design was employed involving 218 certified teachers from Integrated Islamic Elementary Schools (SDIT) in Tangerang City selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that all proposed hypotheses were supported. Local wisdom significantly influenced service quality management (β = 0.732), which subsequently enhanced school image (β = 0.681) and teachers’ adversity quotient (β = 0.594). Furthermore, school image (β = 0.417) and teachers’ adversity quotient (β = 0.385) significantly improved sustainable educational quality, with the structural model explaining 68.7% of the variance (R² = 0.687). The results also confirm that service quality management serves as the primary mediating mechanism through which local wisdom strengthens sustainable educational quality. This study contributes to the development of a culturally grounded educational quality management model and provides practical insights for school leaders and policymakers in promoting sustainable educational improvement.